Water physicochemical factors and oxidative stress physiology in fish, a review - Menon, Soumya V.; Kumar, Avnish; Middha, Sushil Kumar; Paital, Biswaranjan; Mathur, Shivangi; Johnson, Rajee; Kademan, Asha; Usha, Talambedu; Hemavathi, K. N.; Dayal, Sangeeta; Ramalingam, Nirmaladevi; Subaramaniyam, Udayadharshini; et al. (Frontiers in Environmental Science, 2023)
Fish are among the best-studied aquatic animals due to their economic and ecological values. Fish meat is the most affordable protein source for the economically weaker section of people. The environment of almost all aquatic ecosystems has a specific influential role on or by fishes. Therefore, studying their stress biology, especially oxidative stress, is vital because it can influence their growth, production, reproduction, etc. To review the above topic, peer-reviewed electronic databases, including Web of Science, science direct, PubMed, Google Scholar, Scopus, and AGRICOLA, were searched with specific keywords associated with fish, oxidative stress, diseases, etc. The influence of abiotic stress, such as the effects of water DO, temperature, salinity, water hardness, alkalinity, pH, pollutants, heavy metals, and anthropogenic activities, was reviewed in the current article to draw a conclusion on the updated relation that exists between fish physiology, disease, and abiotic stressors. Oxidative stress and redox regulatory levels under the above parameters were reviewed as the stress or anti-stress responses differ in various fish models. Undoubtedly, the reviewed abiotic factors modulate fish oxidative health status to a greater extent, and therefore, these factors must be considered on a priority basis to improve the general health and immunity status of fish. The statement above remains valid in both saline and freshwater habitats.